2018
DOI: 10.1111/jcal.12244
|View full text |Cite
|
Sign up to set email alerts
|

Improving the effectiveness of English vocabulary review by integrating ARCS with mobile game‐based learning

Abstract: Memorizing English vocabulary is often considered uninteresting, and a lack of motivation exists during learning activities. Moreover, most vocabulary practice systems automatically select words from articles and do not provide integrated model methods for students. Therefore, this study constructed a mobile game-based English vocabulary practice system, which imitates the popular block elimination game and combines test items of article, difficulty, and teacher model in accordance with curriculum objectives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 53 publications
5
72
0
2
Order By: Relevance
“…This showed that students with high learning motivation have better learning achievement. The finding of the motivation questionnaire consistent with Wu (2018) that learning motivation enhances competency, which affects greater learning effectiveness.…”
Section: Students Motivationsupporting
confidence: 80%
“…This showed that students with high learning motivation have better learning achievement. The finding of the motivation questionnaire consistent with Wu (2018) that learning motivation enhances competency, which affects greater learning effectiveness.…”
Section: Students Motivationsupporting
confidence: 80%
“…In general, mobile game applications have been used mostly to improve motivation and performance to learn English language skills [11], [14] and many studies have shown that they have gotten a good results and impact [50]- [54]. The mobile game application developed in this study is based on a framework of persuasive guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In the digital age, studies on enhancing learners’ vocabulary learning by using mobile devices have become prevalent. Some studies have been conducted on consolidating vocabulary learning using multimedia messages (Saran et al, 2012), adopting mobile game‐based learning to enhance vocabulary learning in class (eg, Vahdat & Behbahani, 2013; Wu, 2018), improving language learning outside the classroom (Stockwell, 2013) and supporting the learning of idioms ubiquitously across different settings (Foomani & Hedayati, 2016).…”
Section: Related Literaturementioning
confidence: 99%
“…Despite the fact that the number of studies on improving young learners’ language learning supported by mobile technologies both inside and outside classroom has increased in recent years, the majority of these studies has focused on learning for prescribed tasks by following a fixed learning path (eg, Saran, Seferoglu, & Cagiltay, 2012; Wu, 2018). In such learning environments, learners have little room to explore how to make use of the mobile technology affordances on their own to support their learning in real life.…”
Section: Introductionmentioning
confidence: 99%